Experiential writing through connectivism learning theory: a case study of English language students in oman higher education. Issue 3 (4th May 2022) - Al Maawali, Wafaa Saif
ABSTRACT: Despite the widely established importance of connectivism pedagogies in 21 st century learning, there remains a relative dearth of evidence with some expectations on enhancing writing experiences during COVID-19 using online and remote writing mediums. This study aimed to explore how students engage in making sense of their own writing using connectivism learning theory, which allowed them to explore the meaning-making process at personal and collective levels. The study employed a case study design, using data from 43 students enrolled in a first-year enhanced language training (ELT) program; their English levels ranged from 4.0–4.5 International English Language Testing System (IELTS) band scores. The findings of this study suggest that combining both cognitive process theory and connectivism learning theory to teach writing promotes students' reflective practices and deepens their understanding of their writing styles. Furthermore, students' collaborative writing actions led to improvements in their understanding of their approach to text formulation. The findings of this study reveal that connectivism learning theory helped students author longer texts than they usually did, suggesting that writer's blocks for English as a Second Language (ESL) novice writers had reduced. Therefore, this study recommends that teachers should blend a reflective approach to writing with connectivist pedagogies.